Modified graphite material, method for manufacturing the same, secondary battery, and electric device

CN122957831APending Publication Date: 2026-10-23WANHUA CHEM GRP BATTERY TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510479398.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-16
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

其中,固相包覆的优点是工艺简单,但存在包覆均匀性和重复性差问题;液相包覆的优点是包覆层均匀性好,但是污染大,生产成本高;原位聚合包覆通过引发单体聚合形成聚合物包覆在石墨颗粒的表面,最后经干燥和炭化粉碎后得到碳包覆石墨材料,是一种相对较好的包覆方法,但目前的原位聚合包覆工艺存在制备工艺复杂、成本偏高、在原位聚合包覆时因需要强酸/强碱的催化产生较多的废液等问题,而且包覆树脂在热解过程中存在挥发物较多和残炭率低等问题,影响了树脂包覆石墨材料的包覆均匀性,对包覆石墨作为负极材料的锂离子电池的首次效率的提高产生了不利影响

Benefits of technology

[0032]本申请以水性酚醛树脂预聚物作为包覆石墨的碳源,在热解碳化后具有较高的残碳率;同时,水性酚醛树脂预聚物在含水体系中稳定,作为包覆剂以液态的形式加入,更容易与石墨混合均匀。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122957831A_ABST
    Figure CN122957831A_ABST
Patent Text Reader

Abstract

The application discloses a modified graphite material and a preparation method thereof, a secondary battery and an electric device. The preparation method of the modified graphite material comprises the following steps: first, a first aldehyde compound and a phenolic compound are subjected to a first-stage reaction under the action of a first catalyst, and then a second aldehyde compound is added to perform a second-stage reaction to obtain an aqueous phenolic aldehyde resin prepolymer; second, an aqueous diluent of the aqueous phenolic aldehyde resin prepolymer is uniformly mixed with graphite, and then a curing agent or a second aldehyde compound is added to perform a curing reaction to obtain an aqueous phenolic aldehyde resin-graphite mixture; and third, the aqueous phenolic aldehyde resin-graphite mixture is subjected to heat treatment in an inert gas to obtain the modified graphite material. The aqueous phenolic aldehyde resin prepolymer is used as a carbon source for coating graphite, and has a high residual carbon rate after pyrolysis and carbonization; meanwhile, the aqueous phenolic aldehyde resin prepolymer is stable in a water-containing system, and is added in a liquid form as a coating agent, so that the aqueous phenolic aldehyde resin prepolymer is more easily mixed with graphite uniformly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium-ion battery anode material technology, and in particular to a modified graphite material and its preparation method, a secondary battery, and an electrical device. Background Technology

[0002] Graphite, as the most widely used anode material for lithium-ion batteries, has a balanced performance, including relatively low cost, high abundance, high energy density, and good structural stability. However, it also has some issues that need improvement, such as numerous surface defects, high selectivity to electrolytes, high irreversible capacity, and low initial efficiency.

[0003] Currently, the commonly used improvement method is to coat the surface of graphite materials with a layer of carbon material, including solid-phase coating, liquid-phase coating, and in-situ polymerization coating. Among them, solid-phase coating has the advantage of simple process, but suffers from poor coating uniformity and repeatability; liquid-phase coating has the advantage of good coating uniformity, but causes significant pollution and has high production costs; in-situ polymerization coating, which involves initiating monomer polymerization to form polymers that coat the surface of graphite particles, and finally obtaining carbon-coated graphite material after drying and carbonization, is a relatively good coating method. However, current in-situ polymerization coating processes have problems such as complex preparation process, high cost, and the generation of a lot of waste liquid due to the need for strong acid / base catalysis during in-situ polymerization coating. Moreover, the coating resin has problems such as high volatile matter and low carbon residue during pyrolysis, which affect the coating uniformity of resin-coated graphite material and adversely affect the initial efficiency improvement of lithium-ion batteries using coated graphite as a negative electrode material. Summary of the Invention

[0004] This application aims to at least partially address one of the technical problems in the related art.

[0005] Therefore, embodiments of this application propose a modified graphite material and its preparation method, a secondary battery, and an electrical device.

[0006] In a first aspect, this application proposes a method for preparing a modified graphite material, comprising the following steps:

[0007] (1) The first aldehyde compound and the phenolic compound are reacted in the first stage under the action of the first catalyst, and then the second aldehyde compound is added to carry out the second stage reaction to obtain the waterborne phenolic resin prepolymer.

[0008] (2) After the aqueous dilution of the waterborne phenolic resin prepolymer is mixed evenly with graphite, a curing agent or the second aldehyde compound is added to carry out a curing reaction to obtain a waterborne phenolic resin-graphite mixture.

[0009] (3) The aqueous phenolic resin-graphite mixture is heat-treated in an inert gas to obtain a modified graphite material.

[0010] Furthermore, the first aldehyde compound is an aldehyde compound containing a carboxyl group.

[0011] Furthermore, the carboxyl-containing aldehyde compound includes one or both of glyoxylic acid and 3-carboxybenzaldehyde.

[0012] Furthermore, the second aldehyde compound includes aliphatic, cyclic, or aromatic monoaldehyde or dialdehyde compounds, and carboxyl-containing aldehyde compounds having the structural formula X-CHO, wherein X includes one of carboxyl, aryl carboxyl, or C2-C5 alkyl carboxyl.

[0013] Furthermore, the amount of the first aldehyde compound added is 10% to 26% of the mass of the second aldehyde compound.

[0014] Furthermore, the phenolic compounds include one or more of phenol, 1,2-benzenediol, 1,3-benzenediol, and 1,4-benzenediol.

[0015] Furthermore, the phenolic compound has substituents on its benzene ring, including a carboxyl group or a C2-C5 alkylcarboxyl group.

[0016] Furthermore, the first catalyst is an acidic catalyst.

[0017] Furthermore, the acidic catalyst includes one or more of hydrochloric acid, nitric acid, and oxalic acid.

[0018] Furthermore, the amount of the first catalyst added is 0.6% to 2.3% of the mass of the phenolic compound.

[0019] Furthermore, the second catalyst is an alkaline catalyst.

[0020] Furthermore, the alkaline catalyst includes one or more of sodium hydroxide, barium hydroxide, ammonia, or triethylamine.

[0021] Furthermore, the amount of the second catalyst added is 3.1% to 9.0% of the total mass of the phenolic compound, the first aldehyde compound, and the second aldehyde compound.

[0022] Furthermore, the reaction temperature of the first stage reaction is 90–110°C, and the reaction time is 5–10 hours.

[0023] Furthermore, the reaction temperature of the second stage reaction is 65–90°C, and the reaction time is 2–5 hours.

[0024] Furthermore, the heat treatment temperature is 1100–1350°C, and the time is 4–10 hours.

[0025] Furthermore, the median particle size Dv50 of the graphite is 8.0–20.0 micrometers, and D min ≥1.0 micrometers.

[0026] Furthermore, the solid content of the aqueous dilution of the aqueous phenolic resin prepolymer is 20% to 40%.

[0027] Furthermore, the mass ratio of the aqueous dilution of the aqueous phenolic resin prepolymer to the graphite is (0.12-0.3):1.

[0028] Secondly, this application proposes a modified graphite material, which is prepared by the preparation method proposed in the first aspect above.

[0029] Thirdly, this application proposes a secondary battery, including a negative electrode sheet, which is obtained by coating a negative electrode slurry made of a modified graphite material prepared by the preparation method proposed in the first aspect or the modified graphite material proposed in the second aspect onto a negative electrode current collector and then drying it.

[0030] Fourthly, this application proposes an electrical device comprising the secondary battery described in the third aspect above.

[0031] Compared to existing technologies, the beneficial effects of this application are as follows:

[0032] This application uses waterborne phenolic resin prepolymer as the carbon source for coating graphite, which has a high residual carbon rate after pyrolysis and carbonization. At the same time, the waterborne phenolic resin prepolymer is stable in aqueous systems and is added in liquid form as a coating agent, making it easier to mix evenly with graphite.

[0033] This application uses waterborne phenolic resin prepolymer as a coating agent, which has the characteristics of low addition amount, simple operation and uniform coating. It can effectively reduce graphite surface defects and specific surface area, and improve the first efficiency and cycle performance of graphite anode materials for lithium-ion batteries. Attached Figure Description

[0034] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the following description of the embodiments taken in conjunction with the accompanying drawings, wherein:

[0035] Figure 1 This is a flowchart of the preparation method of the modified graphite material of this application. Detailed Implementation

[0036] The embodiments of this application are described in detail below. Examples of these embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain this application, and should not be construed as limiting this application.

[0037] The modified graphite material, its preparation method, secondary battery, and power-consuming device of this application are described below with reference to the accompanying drawings.

[0038] Preparation methods of modified graphite materials, such as Figure 1 As shown, it includes the following steps:

[0039] (1) The first aldehyde compound and the phenolic compound are reacted in the first stage under the action of the first catalyst, and then the second aldehyde compound is added to carry out the second stage reaction to obtain the waterborne phenolic resin prepolymer.

[0040] (2) After the aqueous dilution of the waterborne phenolic resin prepolymer is mixed evenly with graphite, a curing agent or a second aldehyde compound is added to carry out a curing reaction to obtain a waterborne phenolic resin-graphite mixture.

[0041] (3) The waterborne phenolic resin-graphite mixture was heat-treated in an inert gas to obtain modified graphite material.

[0042] In step (1), the first aldehyde compound is a carboxyl-containing aldehyde compound. In some embodiments, the first aldehyde compound is selected from one or two of glyoxylic acid and 3-carboxybenzaldehyde.

[0043] The second aldehyde compound includes aliphatic, cyclic, or aromatic monoaldehyde or dialdehyde compounds, and carboxyl-containing aldehyde compounds having the structural formula X-CHO, wherein X includes one of a carboxyl group, an aryl carboxyl group, or a C2-C5 alkyl carboxyl group. In some embodiments, the second aldehyde compound is selected from one or more of formaldehyde, acetaldehyde, glyoxal, succinaldehyde, glutaraldehyde, benzaldehyde, benzoxaldehyde, and hydroxybenzaldehyde.

[0044] In this application, a first aldehyde compound is added first for a first-stage reaction, and then a second aldehyde compound is added for a second-stage reaction. This allows the first aldehyde compound to react better with phenolic compounds, resulting in a product with a relatively small molecular weight and increased water solubility. When it reacts with the second aldehyde compound, it exhibits higher reactivity.

[0045] In this application, the first aldehyde compound is selected as an aldehyde compound with a carboxyl group, which has good dispersibility in aqueous solution and the oligomer formed by the reaction with the phenolic compound has a certain degree of dispersibility in water. In addition, the catalyst added in the second stage is an alkaline catalyst, which neutralizes the carboxyl group of the first aldehyde compound after the reaction in the first stage to form a salt, thereby making the aqueous dispersion of the phenolic resin prepolymer more stable.

[0046] The amount of the first aldehyde compound added is 10% to 26% of the mass of the second aldehyde compound. A small amount of the first aldehyde compound is added first during the reaction process, allowing the first aldehyde compound and the phenolic compound to undergo the first stage reaction under the action of the first catalyst. Within a suitable range, the amount of the first aldehyde compound added results in better water dispersibility of the generated aqueous phenolic resin prepolymer. If too much of the first aldehyde compound is added, the viscosity of the resulting aqueous phenolic resin prepolymer dispersion will be too high; if too little is added, the stability of the formed aqueous phenolic resin prepolymer dispersion will be slightly poor, and precipitates (or flocculent matter) will form even after a short period of settling (e.g., less than one day).

[0047] Phenolic compounds include one or more of phenol, 1,2-benzenediol, 1,3-benzenediol, and 1,4-benzenediol.

[0048] In some embodiments, the phenolic compound further includes phenolic compounds having substituents on the benzene ring, wherein the substituents include a carboxyl group or a C2-C5 alkylcarboxyl group. In some embodiments, the phenolic compound is selected from one or both of 4-hydroxybenzoic acid and 3-hydroxyphenylacetic acid.

[0049] The first catalyst is an acidic catalyst, including one or more of hydrochloric acid, nitric acid, and oxalic acid. During the first stage of the reaction, the acidic catalyst is added to cause the first aldehyde compound and the phenolic compound to react and form linear oligomers. The amount of the first catalyst added is 0.6% to 2.3% of the mass of the phenolic compound. A suitable amount of the first catalyst ensures that the first stage reaction is not too slow and is more conducive to the second stage reaction. If too much of the first catalyst is added, more base compounds need to be added in the second stage to neutralize it; if too little of the first catalyst is added, the reaction time is too long.

[0050] The second catalyst is an alkaline catalyst, including one or more of sodium hydroxide, barium hydroxide, ammonia, or triethylamine. Adding an alkaline catalyst during the second stage reaction increases the water solubility of the linear oligomers generated in the first stage reaction and accelerates the reaction rate in the second stage. The amount of the second catalyst added is 3.1%-9.0% of the total mass of the phenolic compound, the first aldehyde compound, and the second aldehyde compound. Within a suitable range, the amount of the second catalyst can neutralize the first aldehyde compound and the first catalyst, while also catalyzing the second stage reaction. Excessive addition of the second catalyst may cause thickening or poor stability in the resulting aqueous phenolic resin prepolymer dilution; insufficient addition will result in a slow reaction rate in the second stage.

[0051] The reaction temperature of the first stage is 90-110℃, and the reaction time is 5-10 hours. The first stage reaction is within a suitable temperature and time range, so that the reaction is at a certain rate without producing too many by-products.

[0052] The reaction temperature of the second stage is 65-90℃, and the reaction time is 2-5 hours. The second stage reaction is within a suitable temperature and time range, so that the reaction is at a certain rate without producing too many by-products.

[0053] In step (2), the median particle size Dv50 of graphite is 8–20 micrometers, and D min Graphite with a particle size of ≥1.0 micrometers can be used in battery anode materials when the particle size is within a suitable range; when the particle size of graphite is too large, it is rarely used as the main material of battery anode materials; when the particle size of graphite is too small, it is also rarely used as the main material of battery anode materials.

[0054] The solid content of the aqueous diluent of the water-based phenolic resin prepolymer is 20% to 40%. The solid content of the aqueous diluent of the water-based phenolic resin prepolymer is within a suitable range so that the viscosity of the diluent is not too high while maintaining good stability. When the solid content is too high, the viscosity of the aqueous diluent is high; when the solid content is too low, the stability of the aqueous diluent is poor.

[0055] The mass ratio of water dilution of waterborne phenolic resin prepolymer to graphite is (0.12~0.3):1. Within a suitable range, the mass ratio of water dilution of waterborne phenolic resin prepolymer to graphite has a good coating effect. When the mass ratio is too large, too much coating material may lead to capacity loss. When the mass ratio is too small, less coating material may result in poor coating effect, which in turn affects performance.

[0056] In some embodiments, the equipment used to uniformly mix the aqueous dilution of the waterborne phenolic resin prepolymer with graphite can be a ribbon mixer, a plow mixer, a V-type mixer, or a high-power mixer.

[0057] In some embodiments, an aqueous dilution of the aqueous phenolic resin prepolymer and graphite are mixed using a high-power mixer at a speed of 1000-1500 rpm for 4-8 minutes.

[0058] In some embodiments, the curing agent is selected from paraformaldehyde and hexamethylenetetramine.

[0059] In step (3), the heat treatment can be carried out in a roller kiln, pusher kiln or box furnace. The temperature of the heat treatment is 1100-1350℃ and the time is 4-10 hours. Within the appropriate temperature and time range, the pyrolysis and carbonization reaction can be completed smoothly at a certain rate.

[0060] In some embodiments, the inert gas is nitrogen or argon.

[0061] The present application will be described below with reference to specific embodiments. Unless otherwise specified, the experimental materials and reagents used in the following embodiments are commercially available. Where specific techniques or conditions are not specified in the embodiments, they can be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions.

[0062] All percentages in this application are by weight, unless otherwise stated. The raw materials used in the examples are as follows:

[0063] Phenol (chemically pure, Beijing Bailingwei Technology Co., Ltd.);

[0064] 1,3-Ceramide (chemically pure, Shanghai Aladdin Biochemical Technology Co., Ltd.);

[0065] 3-Hydroxyphenylacetic acid (chemically pure, Shanghai Maclean Biotechnology Co., Ltd.);

[0066] 3-Carboxybenzaldehyde (chemically pure, Beijing Bailingwei Technology Co., Ltd.);

[0067] 4-Hydroxybenzaldehyde (chemically pure, Shanghai Aladdin Biochemical Technology Co., Ltd.);

[0068] Glyoxylic acid (50% aqueous solution, Shanghai Mairui Biochemical Technology Co., Ltd.);

[0069] Formaldehyde (37% aqueous solution, Shanghai Aladdin Biochemical Technology Co., Ltd.);

[0070] Glyoxal (40% aqueous solution, Shanghai Aladdin Biochemical Technology Co., Ltd.);

[0071] Paraformaldehyde (chemically pure, Shanghai Aladdin Biochemical Technology Co., Ltd.);

[0072] Hexamethylenetetramine (chemically pure, Shanghai Aladdin Biochemical Technology Co., Ltd.);

[0073] Oxalic acid dihydrate (Shanghai Mairui Biochemical Technology Co., Ltd.);

[0074] Triethylamine (chemically pure, Xilong Scientific Co., Ltd.);

[0075] Natural graphite (spherical, Qingdao Jinhui Graphite Co., Ltd.);

[0076] Phenolic resin (powder, Dv50 approx. 24 microns, Yierfu Chemical Co., Ltd.).

[0077] Example 1

[0078] (a) Under a nitrogen atmosphere, 188.2 g of phenol and 8.66 g of 3-carboxybenzaldehyde were added to a four-necked flask, heated to 80 °C, and then 34.0 g of an aqueous solution containing 1.1 g of oxalic acid was added dropwise. After reacting for 8 hours at 110 °C, the temperature was lowered to 65 °C, and then 9.2 g of triethylamine and 90.0 g of 37% formaldehyde aqueous solution were added dropwise. The reaction was carried out at 90 °C for 2 hours. Finally, the solution was diluted with 254.6 g of water to obtain a diluted aqueous phenolic resin prepolymer solution with a solid content of 40%.

[0079] (b) Mix 150.0 g of prepolymer diluted with water-based phenolic resin and 1200 g of graphite in a high-power mixer at 1500 rpm for 2 minutes. Then add 97.3 g of 37% paraformaldehyde aqueous solution and continue mixing for 4 minutes. Finally, heat treat the water-based phenolic resin-graphite mixture in a box furnace at 1100°C for 8 hours in a nitrogen atmosphere to obtain coated graphite material.

[0080] Example 2

[0081] (a) Under a nitrogen atmosphere, 188.2 g of phenol, 4 g of 3-carboxybenzaldehyde and 4.0 g of 50% glyoxylic acid aqueous solution were added to a four-necked flask, heated to 80 °C, and then 34.0 g of aqueous solution containing oxalic acid (1.1 g) was added dropwise. After reacting for 8 hours at 110 °C, the temperature was lowered to 65 °C, and then 9.2 g of triethylamine and 90.0 g of 37% formaldehyde aqueous solution were added dropwise. The reaction was carried out at 90 °C for 2 hours. Finally, the solution was diluted with 248.6 g of water to obtain a diluted aqueous phenolic resin prepolymer solution with a solid content of 40%.

[0082] (b) Mix 150.0 g of prepolymer diluted with water-based phenolic resin and 1200 g of graphite in a high-power mixer at 1500 rpm for 2 minutes. Then add 97.3 g of 37% paraformaldehyde aqueous solution and continue mixing for 4 minutes. Finally, heat treat the water-based phenolic resin-graphite mixture in a box furnace at 1100°C for 8 hours in a nitrogen atmosphere to obtain coated graphite material.

[0083] Example 3

[0084] (a) Under a nitrogen atmosphere, 188.2 g of phenol and 14.8 g of 50% glyoxylic acid aqueous solution were added to a four-necked flask, the temperature was raised to 80°C, and then 34.0 g of aqueous solution containing oxalic acid (1.1 g) was added dropwise. After reacting for 8 hours at 110°C, the temperature was lowered to 65°C, and then 14.0 g of triethylamine and 90.0 g of 37% formaldehyde aqueous solution were added dropwise. The reaction was carried out at 90°C for 2 hours. Finally, the solution was diluted with 245.3 g of water to obtain a diluted aqueous phenolic resin prepolymer solution with a solid content of 40%.

[0085] (b) Mix 150.0 g of prepolymer diluted with water-based phenolic resin and 1200 g of graphite in a high-power mixer at 1500 rpm for 2 minutes. Then add 97.3 g of 37% paraformaldehyde aqueous solution and continue mixing for 4 minutes. Finally, heat treat the water-based phenolic resin-graphite mixture in a box furnace at 1100°C for 8 hours in a nitrogen atmosphere to obtain coated graphite material.

[0086] Example 4

[0087] The difference from Example 3 is that in step (a), 360.0 g of the aqueous prepolymer dilution of waterborne phenolic resin and 1200 g of graphite are mixed in a high-power mixer at 1500 rpm for 4 minutes, then 97.3 g of 37% formaldehyde aqueous solution is added and the mixture is mixed for another 4 minutes. Finally, the waterborne phenolic resin-graphite mixture is heat-treated in a box furnace at 1350°C for 4 hours in a nitrogen atmosphere to obtain the coated graphite material.

[0088] Example 5

[0089] (a) Under a nitrogen atmosphere, 188.2 g of phenol and 7.4 g of 50% glyoxylic acid aqueous solution were added to a four-necked flask, the temperature was raised to 80°C, and then 34.0 g of aqueous solution containing oxalic acid (1.1 g) was added dropwise. After reacting for 8 hours at 110°C, the temperature was lowered to 65°C, and then 9.2 g of triethylamine and 100.0 g of 37% formaldehyde aqueous solution were added dropwise. The reaction was carried out at 90°C for 2 hours. Finally, the solution was diluted with 242.6 g of water to obtain a diluted aqueous phenolic resin prepolymer solution with a solid content of 40%.

[0090] (b) Mix 150.0 g of prepolymer diluted with water-based phenolic resin and 1200 g of graphite in a high-power mixer at 1500 rpm for 2 minutes. Then add 97.3 g of 37% paraformaldehyde aqueous solution and continue mixing for 4 minutes. Finally, heat treat the water-based phenolic resin-graphite mixture in a box furnace at 1100°C for 8 hours in a nitrogen atmosphere to obtain coated graphite material.

[0091] Example 6

[0092] (a) Under a nitrogen atmosphere, 188.2 g of phenol and 14.8 g of 50% glyoxylic acid aqueous solution were added to a four-necked flask, the temperature was raised to 80°C, and then 34.0 g of aqueous solution containing oxalic acid (1.1 g) was added dropwise. After reacting for 8 hours at 110°C, the temperature was lowered to 65°C, and then 14.0 g of triethylamine and 90.0 g of 37% formaldehyde aqueous solution were added dropwise. The reaction was carried out at 90°C for 2 hours. Finally, the solution was diluted with 245.3 g of water to obtain a diluted aqueous phenolic resin prepolymer solution with a solid content of 40%.

[0093] (b) Mix 150.0 g of prepolymer diluted with water-based phenolic resin with 1200 g of graphite in a high-power mixer at 1500 rpm for 2 minutes. Then add 56.0 g of 50% hexamethylenetetramine and continue mixing for 2 minutes. Finally, heat-treat the water-based phenolic resin-graphite mixture in a box furnace at 1100°C for 10 hours under a nitrogen atmosphere to obtain the coated graphite material.

[0094] Example 7

[0095] (a) Under a nitrogen atmosphere, 178.8 g of phenol, 15.3 g of 3-hydroxyphenylacetic acid and 7.0 g of 50% glyoxylic acid aqueous solution were added to a four-necked flask, heated to 80 °C, and then 34.0 g of aqueous solution containing oxalic acid (4.4 g) was added dropwise. After reacting for 5 hours at 100 °C, the temperature was lowered to 65 °C, and then 26.3 g of triethylamine and 90.0 g of 37% formaldehyde aqueous solution were added dropwise. After reacting for 5 hours, the solution was finally diluted with 829.4 g of water to obtain a diluted aqueous phenolic resin prepolymer solution with a solid content of 20%.

[0096] (b) Mix 240.0 g of prepolymer diluted with water-based phenolic resin with 1200 g of graphite in a high-power mixer at 1000 rpm for 4 minutes. Then add 107.0 g of 37% paraformaldehyde aqueous solution and continue mixing for 4 minutes. Finally, heat-treat the water-based phenolic resin-graphite mixture in a box furnace at 1200°C for 6 hours in a nitrogen atmosphere to obtain coated graphite material.

[0097] Example 8

[0098] (a) Under a nitrogen atmosphere, 188.2 g of phenol and 12.0 g of 50% glyoxylic acid aqueous solution were added to a four-necked flask, the temperature was raised to 80°C, and then 34.0 g of aqueous solution containing oxalic acid (2.4 g) was added dropwise. After reacting for 10 hours at 90°C, the temperature was lowered to 65°C, and then 15.0 g of triethylamine, 24.5 g of 4-hydroxybenzaldehyde and 73.0 g of 37% formaldehyde aqueous solution were added dropwise. The reaction was carried out at 75°C for 3 hours. Finally, the solution was diluted with 486.3 g of water to obtain a diluted aqueous phenolic resin prepolymer solution with a solid content of 30%.

[0099] (b) Mix 200.0 g of prepolymer diluted with water-based phenolic resin with 1200 g of graphite in a high-power mixer at 1200 rpm for 2 minutes. Then add 97.3 g of 37% paraformaldehyde aqueous solution and continue mixing for 2 minutes. Finally, heat treat the water-based phenolic resin-graphite mixture in a box furnace at 1100°C for 8 hours in a nitrogen atmosphere to obtain coated graphite material.

[0100] Example 9

[0101] The difference from Example 3 is that 159.0 g of 40% glyoxal aqueous solution was used instead of 90.0 g of 37% formaldehyde aqueous solution.

[0102] Example 10

[0103] The difference from Example 3 is that 222.0 g of 1,3-benzenediol was used instead of 188.2 g of phenol.

[0104] Comparative Example 1

[0105] The difference from Example 3 is that the aqueous phenolic resin prepolymer dilution with a solids content of 10% was obtained by diluting with 1981.1 g of water. The dilution was unstable and showed sedimentation and adhesion to the walls after standing for 10 minutes.

[0106] Comparative Example 2

[0107] The difference from Example 7 is that the aqueous phenolic resin prepolymer dilution with a solids content of 50% was obtained by diluting with 136.7 grams of water. The dilution has a higher viscosity and poorer flowability.

[0108] Comparative Example 3

[0109] The difference from Example 1 is that 12.0 g of the aqueous prepolymer dilution of waterborne phenolic resin and 1200 g of graphite are mixed in a high-power mixer at 1500 rpm for 2 minutes, then 97.3 g of 37% formaldehyde aqueous solution is added and the mixture is mixed for another 4 minutes. Finally, the waterborne phenolic resin-graphite mixture is heat-treated in a box furnace at 1100°C for 8 hours in a nitrogen atmosphere to obtain the coated graphite material.

[0110] Comparative Example 4

[0111] The difference from Example 1 is that 480.0 g of the aqueous prepolymer dilution of waterborne phenolic resin and 1200 g of graphite are mixed in a high-power mixer at 1500 rpm for 2 minutes, then 97.3 g of 37% formaldehyde aqueous solution is added and the mixture is mixed for another 4 minutes. Finally, the waterborne phenolic resin-graphite mixture is heat-treated in a box furnace at 1100°C for 8 hours in a nitrogen atmosphere to obtain the coated graphite material.

[0112] Comparative Example 5

[0113] (a) Under a nitrogen atmosphere, 188.2 g of phenol and 1.7 g of 3-carboxybenzaldehyde were added to a four-necked flask, and the temperature was raised to 80 °C. Then, 34.0 g of deionized water containing 1.1 g of oxalic acid was added dropwise. After reacting for 8 hours at 110 °C, the temperature was lowered to 65 °C, and then 4.0 g of triethylamine and 90.0 g of 37% formaldehyde aqueous solution were added dropwise. The reaction was carried out at 90 °C for 2 hours. Finally, the solution was diluted with 244.1 g of water to obtain a diluted aqueous phenolic resin prepolymer solution with a solid content of 40%. The diluted solution was unstable and showed sedimentation and adhesion to the walls after standing for 10 minutes.

[0114] Comparative Example 6

[0115] (a) Under a nitrogen atmosphere, 188.2 g of phenol and 20.0 g of 50% glyoxylic acid aqueous solution were added to a four-necked flask. The temperature was raised to 80°C, and then 34.0 g of deionized water containing 1.1 g of oxalic acid was added dropwise. The temperature was then raised to 110°C and reacted for 8 hours. After that, the temperature was lowered to 65°C, and then 17.9 g of triethylamine and 90.0 g of 37% formaldehyde aqueous solution were added dropwise. The reaction was carried out at 90°C for 2 hours. Finally, the solution was diluted with 245.3 g of water to obtain a diluted aqueous phenolic resin prepolymer with a solid content of 40%. The diluted solution had a high viscosity and poor flowability.

[0116] Comparative Example 7

[0117] The graphite material used is uncoated natural graphite with a Dv50 of 15.6 micrometers and a specific surface area of ​​7.96 m². 2 / g.

[0118] Comparative Example 8

[0119] Mix 96.0 g of phenolic resin powder with 1200 g of graphite in a high-power mixer at 1500 rpm for 8 minutes, and then heat-treat in a box furnace at 1200°C for 10 hours in a nitrogen atmosphere to obtain coated graphite material.

[0120] Test case

[0121] The specific surface area and average particle size of the graphite materials in Examples 1-10 and Comparative Examples 1-8 were tested. Coin cells were prepared using the graphite materials, and the first efficiency and capacity retention rate of the coin cells after 100 cycles at 0.1C were tested. The test results are shown in Table 1 below.

[0122] Among them, a Malvern-Mastersizer 3000 laser particle size analyzer was used, and the average particle size was measured according to GB / T 24533-2019 "Graphite Anode Materials for Lithium-ion Batteries" using a wet sampler. A BSD 3H-2000A dynamic specific surface area analyzer was used, and the specific surface area data was obtained according to GB / T 19587-2017 "Determination of Specific Surface Area of ​​Solid Materials by Gas Adsorption BET Method". The samples were pretreated by vacuum degassing at 200℃ for 2 hours. The initial efficiency and capacity retention were tested according to GB / T 24533-2019 "Graphite Anode Materials for Lithium-ion Batteries".

[0123] The preparation process of the button half-cell is as follows: (1) (Modified) graphite / carbon black / styrene-butadiene rubber / hydroxymethyl cellulose are added in a mass ratio of 95.5 / 1.5 / 1.5 / 1.5 and stirred evenly in water to make a negative electrode slurry. Then the slurry is coated on battery-grade copper foil and dried in a vacuum oven at 110°C for 4 hours. Carbon-coated graphite negative electrode sheet is made by rolling and cutting. (2) The counter electrode is a lithium metal sheet, the separator is polyethylene, and the electrolyte includes LiPF6 with a molar concentration of 1 mol / L and solvent (the solvent includes ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate, with a volume ratio of 1 / 1 / 1) to prepare the button half-cell.

[0124] Table 1

[0125]

[0126] According to Examples 1-10 and Comparative Examples 3, 4, 7, and 8, graphite coated with waterborne phenolic resin and graphite coated with phenolic powder resin both have a lower specific surface area, higher initial efficiency, and better cycle performance than uncoated graphite. This indicates that the surface defects of graphite are reduced after modification, resulting in improved performance as a negative electrode material.

[0127] According to Examples 3, 1, 1, 5, and Comparative Examples 1 and 5, when the solid content of the aqueous phenolic resin prepolymer diluent is low or the amount of the first aldehyde compound added is too low, the stability of the diluent is poor and it cannot be stored for a long time.

[0128] According to Examples 7, 3, 2, and 6, when the solid content of the aqueous phenolic resin prepolymer diluent is high or the amount of the first aldehyde compound added is too high, the viscosity of the diluent is high and the fluidity is poor, which is not conducive to the coating operation.

[0129] Based on Examples 1 and Comparative Examples 3 and 4, it can be seen that the mass ratio of the diluent to graphite in Comparative Example 3 is too low, resulting in less coating agent. Therefore, it can only partially repair the surface defects of graphite, leading to a decrease in specific surface area and an improvement in initial efficiency that is not as good as in Example 1. The mass ratio of the diluent to graphite in Comparative Example 4 is too high. Although the decrease in the specific surface area of ​​the graphite substrate is more obvious, the initial efficiency and cycle performance are not as good as in Example 1.

[0130] According to Examples 1-6 and Comparative Example 8, when the same mass of aqueous phenolic resin is added based on solid content, compared with Comparative Example 8, the graphite substrate in the examples has a lower specific surface area, higher initial efficiency, and improved cycle performance. This is mainly because the larger particles of phenolic resin in the aqueous phenolic resin dispersion have better mixing and coating uniformity with the graphite, thus resulting in better performance.

[0131] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms may refer to different embodiments or examples. Furthermore, the specific features, structures, materials, or characteristics described may be combined in a suitable manner in any one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0132] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0133] Although embodiments of this application have been shown and described, those skilled in the art will understand that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of this application, the scope of which is defined by the claims and their equivalents.

Claims

1. A method for preparing a modified graphite material, characterized in that, Includes the following steps: (1) The first aldehyde compound and the phenolic compound are reacted in the first stage under the action of the first catalyst, and then the second aldehyde compound is added to carry out the second stage reaction to obtain the waterborne phenolic resin prepolymer. (2) After the aqueous dilution of the waterborne phenolic resin prepolymer is mixed evenly with graphite, a curing agent or the second aldehyde compound is added to carry out a curing reaction to obtain a waterborne phenolic resin-graphite mixture. (3) The aqueous phenolic resin-graphite mixture is heat-treated in an inert gas to obtain a modified graphite material.

2. The preparation method according to claim 1, characterized in that, The first aldehyde compound is an aldehyde compound containing a carboxyl group; And / or, the second aldehyde compound includes aliphatic, cyclic or aromatic monoaldehyde or dialdehyde compounds, or carboxyl-containing aldehyde compounds having the structural formula X-CHO, wherein X includes one of carboxyl, aryl carboxyl, or C2-C5 alkyl carboxyl. And / or, the amount of the first aldehyde compound added is 10% to 26% of the mass of the second aldehyde compound; And / or, the phenolic compounds include one or more of phenol, 1,2-benzenediol, 1,3-benzenediol, and 1,4-benzenediol.

3. The preparation method according to claim 2, characterized in that, The phenolic compound has substituents on its benzene ring, including a carboxyl group or a C2-C5 alkylcarboxyl group.

4. The preparation method according to claim 1, characterized in that, The first catalyst is an acidic catalyst; And / or, the acidic catalyst includes one or more of hydrochloric acid, nitric acid, and oxalic acid; And / or, the amount of the first catalyst added is 0.6% to 2.3% of the mass of the phenolic compound; And / or, the second catalyst is a basic catalyst; And / or, the alkaline catalyst includes one or more of sodium hydroxide, barium hydroxide, ammonia, or triethylamine; And / or, the amount of the second catalyst added is 3.1% to 9.0% of the total mass of the phenolic compound, the first aldehyde compound, and the second aldehyde compound.

5. The preparation method according to claim 1, characterized in that, The reaction temperature of the first stage is 90–110℃, and the reaction time is 5–10 hours; And / or, the reaction temperature of the second stage reaction is 65–90°C, and the reaction time is 2–5 hours; And / or, the heat treatment temperature is 1100–1350°C, and the time is 4–10 hours.

6. The preparation method according to claim 1, characterized in that, The median particle size Dv50 of the graphite is 8.0–20.0 micrometers, and D min ≥1.0 micrometers.

7. The preparation method according to claim 1, characterized in that, The solid content of the aqueous dilution of the aqueous phenolic resin prepolymer is 20% to 40%. And / or, the mass ratio of the aqueous dilution of the aqueous phenolic resin prepolymer to the graphite is (0.12-0.3):

1.

8. A modified graphite material, characterized in that, The modified graphite material is prepared by the preparation method described in claims 1 to 7.

9. A secondary battery, comprising a negative electrode, characterized in that, The negative electrode sheet includes a negative current collector and a layer of negative active material disposed on the negative current collector, wherein the negative active material includes the modified graphite material prepared by the preparation method according to claims 1 to 7 or the modified graphite material according to claim 8.

10. An electrical appliance, characterized in that, Includes the secondary battery as described in claim 9.